Peningkatan Akurasi Algoritma C4.5 Menggunakan Particle Swarm Optimization Untuk Mendeteksi Penyakit Diabetes - I Gusti Bagus Ari Sidi Mantra Arsana; Ridowati Gunawan (Bit (Fakultas Teknologi Informasi Universitas Budi Luhur), 2022)
Diabetes is a disease that occurs due to an increase in blood sugar levels. Increased sugar levels can trigger death because they can cause damage to blood vessels, nerves, and other internal structures. To avoid bad consequences, it is important to predict whether a person has diabetes or not based on the information that each patient has. The method that can be used to predict whether someone has diabetes or not is a classification method. The C4.5 algorithm is one of the classification algorithms that can be used to predict diabetics. Although the C4.5 algorithm can be used to predict, getting a high accuracy value is also an important measurement. One thing that can be done to increase the accuracy value is to select the attribute that most influences a person to have diabetes or not. Feature selection greatly affects the accuracy of the C4.5 algorithm, particle swarm optimization is used as a feature selection method in this study. The purpose of this study is to increase the value of accuracy to predict whether someone has diabetes or not through feature selection using particle swarm optimization. The dataset used is the Pima Indian Diabetes Databases (PIDD) from the University of California Irvine (UCI) Machine Learning Repository. The results of the study show that feature selection using particle swarm optimization before using the C4.5 algorithm can increase accuracy by 6% from the previous accuracy value of 75%. The selected features are 4 attributes out of 9 attributes. The four attributes are Glucose, SkinThickness, BMI, and DiabetesPedigreeFunction. The results of feature selection using particle swarm optimization can increase the accuracy of predictions of whether someone suffering from diabetes or not.